Grievance Arbitration and the Charter: The Emerging Issues - Carter, Donald (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1989)
The Charter has had the effect of casting a long shadow of uncertainty over our established industrial relations institutions. Nowhere is this more true than in the area of grievance arbitration. In this paper, the author deals with the issues at stake, and the reasons why bot h arbitrators and judges are having such difficulty in deciding upon the extent to which grievance arbitration should be influenced by the Charter.